2014
DOI: 10.5604/12321966.1120613
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Physical Fitness, BMI, physical activity and time spent at a computer screen in 6 and 7-year-old children from rural areas in Poland

Abstract: The objective of the study was determination of the effect of various forms of physical activity, BMI, and time devoted to computer games on the level of Health-Related Physical Fitness (H-RF) in 6-7-year-old children from Polish rural areas. The study covered 25,816 children aged 6-7: 12,693 girls and 13,123 boys. The evaluations included body height and weight, and 4 H-RF fitness components (trunk strength, explosive leg power, arm strength and flexibility). The BMI was calculated for each child. The Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…Higher duration or frequency of screen time (2/2 studies) and computer use (2/2 studies) were also significantly associated with lower muscular strength/endurance (Ciesla et al 2014;Grontved et al 2013;Tucker et al 2014). For 1 study, significant findings were observed for explosive leg power and lower trunk power but not for strength of arm (Ciesla et al 2014). Mainly null findings were observed for accelerometer-derived sedentary time, TV viewing, and video game use with muscular strength/endurance.…”
Section: S253 Published By Nrc Research Pressmentioning
confidence: 52%
See 2 more Smart Citations
“…Higher duration or frequency of screen time (2/2 studies) and computer use (2/2 studies) were also significantly associated with lower muscular strength/endurance (Ciesla et al 2014;Grontved et al 2013;Tucker et al 2014). For 1 study, significant findings were observed for explosive leg power and lower trunk power but not for strength of arm (Ciesla et al 2014). Mainly null findings were observed for accelerometer-derived sedentary time, TV viewing, and video game use with muscular strength/endurance.…”
Section: S253 Published By Nrc Research Pressmentioning
confidence: 52%
“…Furthermore, inconsistent findings were observed for accelerometer-derived sedentary time and primarily null findings were observed for computer use with cardiorespiratory fitness. Higher duration or frequency of screen time (2/2 studies) and computer use (2/2 studies) were also significantly associated with lower muscular strength/endurance (Ciesla et al 2014;Grontved et al 2013;Tucker et al 2014). For 1 study, significant findings were observed for explosive leg power and lower trunk power but not for strength of arm (Ciesla et al 2014).…”
Section: S253 Published By Nrc Research Pressmentioning
confidence: 67%
See 1 more Smart Citation
“…, 25 , 27 Approximately 90% of obesity cases are considered idiopathic and 10% are attributed to hormonal and genetic causes. The latest advances in research indicate the participation of leptin, the hypothalamic melanocortin receptor 4 and mitochondrial uncoupling proteins in the pathogenesis of obesity/overweight, which opens new possibilities for the successful therapeutic management of these conditions,29 especially in cases of severe obesity and when measures aimed at changing habits and lifestyle were not successful.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos autores ya habían encontrado estas correlaciones previamente, tanto con metodologías objetivas (22) como a través de cuestionarios (23). Las asociaciones positivas con el resto de componentes de la condición física estudiados también coinciden con otros estudios previos (24), aunque nuestros resultados muestran unas correlaciones mucho más fuertes.…”
Section: Discussionunclassified